If the coefficient of x^2 is 1, look for 2 numbers which when multiplied give you the constant, and which when added give you the coefficient of the middle term
that is,
(-10)(4) = -40
(-10) + 4 = -6
so (x - 10)(x + 4)
for the second one: 3x^2 + 20x - 7 = 0 ,
what method have you learned.
I hesitate to give you a solution using a method you do not know.
Have you learned decomposition?
1a) Solve each of these questions by factorising the left hand side into a product of linear factors:
(i) x^2 - 6x - 40 = 0
(ii) 3x^2 + 20x - 7 = 0
For each question in part (a), check your solutions by substituting them back in to the equation.
2 answers
No I haven't